Pengaruh PBV Dan DER Dengan PER Sebagai Intervening Terhadap Harga Saham Pada Perusahaan Sektor Farmasi - Hariadi Rizky Prestasi Akbar; Mulyanto Nugroho (Universitas Katolik Widya Karya Malang, 2024)
Analyzing the impact of PBV, DER, and PER on stock prices, including the influence of PBV and DER on PER, and the intervening role of PER in the PBV and DER dynamics, this study involves nine pharmaceutical companies listed on the Indonesia Stock Exchange, utilizing SmartPLS software. Findings indicate PBV significantly affects stock prices, whereas DER and PER show negligible impact. Both PBV and DER do not influence PER, and PER refrains from intervening in the interplay between PBV and DER concerning stock prices. Despite investor assessments prioritizing book value over indebtedness, the EPS-represented stock acquisition holds minimal influence on investor decisions, leading to PER's inconspicuous impact on stock prices. Contributions of DER and PER to stock values, implications of PBV and DER on PER, and PER's intervening role in the PBV-DER dyad have relatively small effects on stock prices. Consequently, the hypotheses, except for PBV's distinctive influence on stock valuations, are rejected in this intricate analysis.